The Critical Survey of Evolution in Common Persian Slang Lexicography “By Emphasizing on Twelve Common Persian Slang Lexicons” - Ghodsie Rezvanian; Siyavash Haghjoo; Leila Darvish Ali Pour Astaneh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
From Ghaghara era up to now, around 60 lexicons gathered but unawareness to methods and configuration of methods in micro and major structure for lexicography, the old approach to slang, low vision to slang in comparison with formal language, fear of destroying taboo words in formal language from cultural statecraft which caused more gathering merchant lexicon and unnoticed in university meetings. The territory of this essay is describing and criticizing twelve main lexicon in Persian slang from 60 lexicons by the usage of practical linguistics science. The results of this essay anecdote that 12 lexicons are adapted by Lexicography methods in formal language and the highest weakness of lexicographers is incorrect or defective information of sub enters in micro and major structure. This essay attempts to survey texts of 12 lexicons, assuming that the use of formal language Lexicography and Personal Computer (PC) Figuration can aid to protect and give scientific credit to this temporary language.